MO816PULSE PRESSURE IS AN INDEPENDENT PREDICTOR OF THE RISK OF RECURRENT ALL-CAUSE HOSPITALIZATION IN CHRONIC HEMODIALYSIS PATIENTS. (29th May 2021) - Mermelstein, Ariella; Cherif, Alhaji; Zhang, Hanjie; Ye, Xiaoling (Janice); Kotanko, Peter; Raimann, Jochen
Abstract: Background and Aims: Pre - and peri-dialytic systolic blood pressures (SBP) have been linked to heightened cardiovascular morbidity and mortality in hemodialysis (HD) patients. High pulse pressure (PP) is clinically associated with increased arterial stiffness and atrial fibrillation, while low PP is associated with cardiac insufficiency. We studied the relationship between PP and all-cause hospitalization in patients undergoing maintenance HD. Method: This retrospective cohort study was performed in HD patients from January 2015 to May 2020. To be included in the study, patients were required to be 18 or older, dialysis vintage of at least a year, and must have received treatment within the first 30 days after dialysis initiation. We developed Cox proportional hazards models with spline corrected terms for recurrent all-cause hospitalizations. 95% confidence interval (CI) were also computed. Further, we stratified the patient population into 4 SBP categories, namely: SBP < 120, 120 ≤ SBP < 150, 150 ≤ SBP < 180, and SBP ≥ 180 mmHg, and investigated the mediating effects of SBP on hospitalization risk. Results: We studied 2453 HD patients (age 58.9±16.1 years, 58% male) dialyzed between January 2014 and October 2018 in Renal Research Institute facilities. We observe that PPs between 45 and 70 mmHg were associated with lower risk of recurrent hospitalization (Figure 1a ), possibly driven by the behavior of SBPs between 120 to 180 mmHg (Figure 1c-e ). No statistically significant association was seen between PP and hospitalization for patients with SPB <120mmHg and >180mm (Figures 1b-d ). A decreasing trend with PP greater than 90mmHg is noted but rendered negligible, and a statistical artifact caused by a case mix at these unusually high levels. The lack of significant associations between inflammatory (NLR) and nutritional (Albumin and phosphorus) factors renders PP a significant and independent predictor of recurrent hospitalization adding to the current knowledge in the field. Conclusion: Our analysis found associations between PP (with and without SBP stratification) and the risk of recurrent hospitalization and all-cause mortality. Even after adjustment for hospitalization risk and other clinical, inflammatory, and nutritional parameters at baseline PP remained an independent predictor of recurrent hospitalizations. Further investigations into the relationship are needed to better understand the mediating effects of PP as a driver of hospitalization and mortality risk.